Whole System Design of a Wearable Magnetic Induction Sensor for Physical Rehabilitation. (26th June 2019) - Chen, Liming; Lu, Mingyang; Wang, Yuqi; Huang, Yuhao; Zhu, Shuang; Tang, Jiawei; Zhu, Chuang; Liu, Xuqing; Yin, Wuliang
Abstract : In article number 1900037, Xuqing Liu, Wuliang Yin, and co‐workers propose a systematic design of magnetic induction sensor, involving materials preparation via new surface nanotechnology, assemble process optimization by waxing, signal acquisition and analysis via novel equipment, and theoretical considerations in electromagnetics to support joint rehabilitation motion results.